Energy-Efficient Cognitive Wireless Sensor Networks Under Spectrum Handoff - Ahmed, Arifa; Mishra, Deepak; Ranjan Behera, Bikash; Saini, Ravikant (IEEE sensors journal, 2025)
To address the increasing demand for sensors and their applications, cognitive radio (CR) technology has been integrated into sensors, leading to the development of cognitive wireless sensor networks (WSNs). This technology, particularly in the interweave CR paradigm, allows sensors to utilize the licensed spectrum of primary users (PUs) dynamically without causing interference, thus improving spectrum utilization. However, in cognitive WSNs, maintaining seamless connectivity between sensors necessitates spectrum handoff, which can be energy-intensive and negatively impact energy efficiency (EE) performance. This study formulates a joint optimization problem of frame duration and transmit power to optimize the EE of a sensor in a cognitive WSN while taking spectrum handoff into consideration, with potential applications in 6G networks and the Internet of Things (IoT). The optimization problem is formulated with practical constraints, including interference resulting from PU's reoccupation during the transmission of the sensor and the transmit power of the sensor, while reliable sensing performance is ensured through target detection and false alarm probabilities. To identify the joint optimal solution of the proposed optimization problem, we develop an alternating optimization method with low complexity. The numerical results demonstrate that the proposed algorithm performs comparably to the exhaustive search technique, confirming its effectiveness. Furthermore, our approach outperforms the benchmark fixed allocation scheme by about 2.5 times, showing a notable average improvement in EE.